PENGOLAHAN LIMBAH MINYAK JELANTAH MENJADI LILIN AROMATERAPI DI BANK SAMPAH LINTAS WINONGO, KELURAHAN BUMIJO, KECAMATAN JETIS, KOTA YOGYAKARTA - Astuti, Amalia Yuli; Linarti, Utaminingsih; Indah Budiarti, Gita (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2021)
Waste Cooking Oil (WCO) is the waste that came from household. WCO become a threat to community because it will come back to food chains again as residual bulk oil that have cheaper price than branded cooking oil. Lintas Winongo Waste Bank in Bumijo, Jetis, Yogyakarta City are trying to manage the waste cooking oil into recycled products. One of their products is aromatherapy candles. However, they had problem to produce the candles and sell it. They also faced problem about the odor of candle that came from WCO as raw material. The purpose of community service were to provide knowledge and skills to produce aromatherapy candles and to calculate the Cost of Goods Sold (CoGS). The methods in this activity were carried out in two stage. The first activity has organized by training and assistance in producing aromatherapy candles that mixed WCO and other ingredients. The second activity focused in calculating CoGS of candles. The results from these community service activities were increased knowledge and skills about producing aromatherapy candles. There were also increased knowledge about manage CoGS of their products